A methodology to manage and monitor social media inside a company: a case study. Issue 2 (2014) - Elena Alberghini; Livio Cricelli; Michele Grimaldi
<x xml:space="preserve"> Abstract </x> Purpose – This paper aims to discuss the individual participation and involvement affecting the user engagement in social media and to answer the following research questions: Is it possible to measure the individual participation and involvement of social media within organizations? Which factors should be analysed in order to increase the individual participation in social media? Which KPIs should be selected in order to increase the user's engagement and increase individual participation in social media? Can social media in a company be measured in terms of their impact on KM?Design/methodology/approach – This paper presents a case study that describes how Key Performance Indicators (KPIs) are used to monitor and manage the applications of social technologies, which include many tools facilitating the participation and collaboration on the web. The case study was applied to the information and communication technology area of Eni S.p.A., which is an integrated energy company active in over 70 countries in the world.Findings – Based on the indications obtained from the case study, a methodology is proposed to select and develop the appropriate KPIs in order to manage and monitor the application of social technologies. The methodology turned out to be able to monitor collaboration and knowledge sharing activities among employees and to incentivize participation and involvement of employees who use the company's social media.Practical implications – Organizations can use the suggested methodology as a guideline for managing and monitoring social media inside a company. The possibility of continuously modifying the adopted social media tool by means of corrective actions together with the possibility of adapting the KPIs to new situations make the present methodology an efficient management approach to take on the multifaceted activities of a social media environment.Originality/value – Few case studies dealing with the applications regarding the implementation and management of social technologies within organizations have been carried out. Similarly, even if some empirical studies have been proposed to analyse what motivates and prevents employees from sharing their knowledge through social media, there appears to be a lack of studies which have taken into consideration the evaluation of the actual benefits in terms of individual involvement and participation, knowledge sharing and increase in performance. <ack> <x xml:space="preserve"> Acknowledgements </x> Received 15 October 2013. Revised 13 January 2014, 17 January 2014. Accepted 19 January 2014. </ack>